Brainstem anesthesia: A rare complication after peribulbar anesthesia - Chaitali Basu,; Samir Basak, (Indian Journal of Case Reports, 2021)
Brainstem anesthesia (BSA) is a rare but serious complication of the peribulbar block. Fewer than ten cases have been reported in the literature. We report a case of BSA after the peribulbar block for cataract surgery. The patient developed convulsion and respiratory arrest 5 min after injection of 7 ml of 2% lignocaine using a 25 ml (mm) length of 24 gauge (G) needle. The patient was successfully managed with prompt recognition and mechanical ventilation for about 1 h. Cataract surgery was performed 3 months after the adverse event. This time, the patient had an uneventful recovery. The patient was well at the 6-month follow-up.